2018
DOI: 10.1515/hukin-2017-0191
|View full text |Cite
|
Sign up to set email alerts
|

Successful and Unsuccessful Offensive Sequences Ending in a Shot in Professional and Elite Under-16 Basketball

Abstract: Following observational methodology, we analyzed successful and unsuccessful offensive attacks by professional and elite under-16 (U16) basketball players in Spain using an adapted ad hoc observation instrument designed to study efficiency in basketball. We identified both similarities and differences between how players from both categories built their attacks. The synchronic statistical analysis based on frequency counts showed that shots were more efficient in professional basketball and that U16 basketball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…The findings in this tournament show that the best performances when executing these game actions (1-on-1 and BS) were obtained with not defended shots close to the basket, confirming conclusions from other studies [ 5 , 10 , 32 , 35 ], and, if close shots were not possible, they tried to go for not defended shots towards the centre of the court, as suggested by other researches analysing finishes in carrying the ball in these kinds of situations [ 8 , 26 , 27 , 28 ]. In the same line, it is normal that the spaces towards the corners are not very frequent.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings in this tournament show that the best performances when executing these game actions (1-on-1 and BS) were obtained with not defended shots close to the basket, confirming conclusions from other studies [ 5 , 10 , 32 , 35 ], and, if close shots were not possible, they tried to go for not defended shots towards the centre of the court, as suggested by other researches analysing finishes in carrying the ball in these kinds of situations [ 8 , 26 , 27 , 28 ]. In the same line, it is normal that the spaces towards the corners are not very frequent.…”
Section: Discussionsupporting
confidence: 90%
“…The first finding of the research identified the open (not defended) shot at basket as the first predictive variable of success in positional 5-on-5 situations against an individual defence, as reported by other research in other contexts [ 7 , 10 , 12 , 35 ]. These data would allow us to think about the fact that, if the coach’s OS encourages cooperation strategies among the players of his team, it can favour the obtaining of open shots (not contested) [ 4 , 8 ], which means that playing with passes could help with being more effective in possessing, as other investigations in different contexts already stated [ 8 , 11 , 16 , 30 ].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Another explanation addresses the peculiarities of game pace in youth basketball. Previous research demonstrated that elite youth basketball teams played less static and exhibit a higher frequency of fastbreaks compared to professional adult basketball teams [ 62 ]. With higher game pace, inaccuracies (e.g., turnovers) increase [ 4 ] which may affect the assist-turnover-ratio in the present study.…”
Section: Discussionmentioning
confidence: 99%